2017
DOI: 10.1002/app.44912
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinking and post‐crosslinking of ethylene vinyl acetate in photovoltaic modules

Abstract: Ethylene vinyl acetate (EVA) is the dominating material for the encapsulation of solar cells. A better understanding of the crosslinking reaction progress during PV module lamination could lead to promising approaches for shortening of PV module lamination times but also for optimization of the EVA formulation. Therefore, the main aim of this study is to investigate the crosslinking behavior of EVA but also for optimization potentials of the EVA formulation. Currently, a degree of crosslinking higher than 70% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…Presumably, these leftovers of peroxides react with silver which leads into the corrosion of finger and busbar conduction lines as observed in modules Maged and Mexpired. This is in good agreement with other studies published in literature, where several authors reported a correlation between poorly crosslinked EVA and discoloration of soldering ribbons as well as corrosion of the silver gridlines [24]- [27]. The observed degradation effects have been explained by the high amount of still reactive peroxides in the modules which can react either directly with the surface of the metallic PV module components or with degradation products of the EVA encapsulant like acetic acid and subsequently lead to a corrosion of the soldering material or the silver grid lines.…”
Section: Eva Film Characterisationsupporting
confidence: 93%
“…Presumably, these leftovers of peroxides react with silver which leads into the corrosion of finger and busbar conduction lines as observed in modules Maged and Mexpired. This is in good agreement with other studies published in literature, where several authors reported a correlation between poorly crosslinked EVA and discoloration of soldering ribbons as well as corrosion of the silver gridlines [24]- [27]. The observed degradation effects have been explained by the high amount of still reactive peroxides in the modules which can react either directly with the surface of the metallic PV module components or with degradation products of the EVA encapsulant like acetic acid and subsequently lead to a corrosion of the soldering material or the silver grid lines.…”
Section: Eva Film Characterisationsupporting
confidence: 93%
“…For EVA and POE, an exotherm peak starting around 125 C due to the decomposition of the cross-linking agent can be seen before lamination. 8,9 The In the first TMA heating run, all three types of encapsulants showed thermal expansion in both directions (machine direction MD and cross direction CD) indicating biaxial orientation, which is common in solar applications since it leads to better mechanical, optical and barrier properties. 52 However, for all test modules, yellowing was observed after DH test and the strongest for the material stacks using TPO as encapsulant (see Figure 7).…”
Section: Introductionmentioning
confidence: 99%
“…5 To achieve thermal and thermo-mechanical stability, the material is equipped with curing agents (peroxides) for chemical cross-linking to take place during the lamination process, where a three-dimensional polymer network is formed. [8][9][10][11][12] After this time-and energy-consuming module lamination process, it also leaves reactive peroxides in the PV module, which can influence or accelerate certain degradation modes. 9,13,14 Another drawback of EVA is the formation of acetic acid during chemical degradation of EVA, 5,15 which also accelerates the oxidation process of EVA.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations